Under an unlucky star: Astrological Prognostications and repertories censored by the Spanish Inquisition (1632-1707) - Mathilde ALBISSON (Studia Historica: Historia Moderna, 2019)
This paper deals with an aspect of the confrontation between astrology and inquisitorial censorship, which took place from the last third of the 16th to the 18th century: it focuses on the prognostications and astrological repertories that were censored by the Spanish Inquisition in the 17th century. This widespread literature in vernacular language was the target of the Holy Office due to its frequent incursions into the field of the prohibited judicial astrology. The paper investigates the passages that were subject to expurgation or inquisitorial suspicion and the motive of the censorship, in the light of the censorial files. This study aims to characterise the Spanish Inquisition attitude towards a popular astrological literature and to identify what is the rationale behind the control of its abundant editorial production.